Prognostic performance of examined lymph nodes, lymph node ratio, and positive lymph nodes in gastric cancer: a competing risk model study - Xiao Gu; Yaqi Du (Frontiers in Endocrinology)
BackgroundPrevious research on the prognostic effectiveness of examined lymph nodes (ELN), lymph node ratio (LNR), and positive lymph nodes (pN) in postoperative gastric cancer (GC) has yielded inconsistent results despite their widespread use.MethodsThis study used a competing risk model (CRM) to evaluate the prognostic efficacy of these markers in patients with GC. Data from 337 patients with lymph node (LN)-positive stage II GC undergoing resection and chemotherapy between 2010 and 2015 were collected from the Surveillance, Epidemiology, and End Results database. Optimal cutoff values for ELN and LNR were determined using restricted cubic splines, and pN was divided into three groups based on the AJCC staging system. The survival analyses were conducted using Kaplan–Meier curves, Cox proportional hazards analysis, cumulative incidence curves, and CRM. Subgroup analysis and interaction tests were performed to evaluate the correlation between LN status and survival within subgroups.ResultsThe results indicated that the optimal cutoff values for ELN, LNR, and pN were 16, 0.1, and 2. Multivariate Cox analysis showed that ELN (hazard ratio [HR] = 0.67), LNR (HR = 2.23), and pN (HR = 2.80) were independent predictors of overall survival, whereas only LNR (HR = 2.08) was independently associated with disease-specific survival. The CRM revealed that LNR (sub-distribution hazard ratio [SHR] = 1.89) and pN (SHR = 2.80) were independently associated with disease-specific survival.ConclusionIn conclusion, ELN, LNR, and pN are all significant predictors of overall survival for GC. However, LNR demonstrates stronger robustness in predicting DSS than ELN and pN. The LNR may supplement the TNM staging system in identifying prognostic discrepancies.